Commonwealth Secretariat publications - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Commonwealth Secretariat's 1989 publications list contains new and recent titles, as well as works already or regularly published. It contains a range of information material on Commonwealth organizations and their activities; research studies;...